2020
DOI: 10.2147/idr.s263632
|View full text |Cite
|
Sign up to set email alerts
|

<p>Loss of Taste and Smell are Common Clinical Characteristics of Patients with COVID-19 in Somalia: A Retrospective Double Centre Study</p>

Abstract: Purpose The purpose of this study was to identify the common clinical presentations and the evidence on the presence of ageusia and anosmia as an emerging coronavirus disease 2019 (COVID-19) symptom to better inform in both COVID-19 patients and clinicians. Patients and Methods As part of a double-institutional collaboration coordinated by doctors, this study retrospectively collected and analyzed the clinical characteristics of 60 patients with COVID-19 pneumonia betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13 , 51 96 , Egypt 97 , France 98 101 , Germany 102 , India 103 , 104 , Italy 105 111 , Japan 112 , 113 , Jordan 114 , Somalia 115 , South Korea 116 , 117 , Spain 118 , 119 , Turkey 120 , 121 , and the US 122 126 . Two studies were cross-sectional 119 , 122 , five were prospective cohort studies 65 , 90 , 98 , 110 , 121 and the remaining 71 studies were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13 , 51 96 , Egypt 97 , France 98 101 , Germany 102 , India 103 , 104 , Italy 105 111 , Japan 112 , 113 , Jordan 114 , Somalia 115 , South Korea 116 , 117 , Spain 118 , 119 , Turkey 120 , 121 , and the US 122 126 . Two studies were cross-sectional 119 , 122 , five were prospective cohort studies 65 , 90 , 98 , 110 , 121 and the remaining 71 studies were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 78 studies were included to calculate the prevalence of headache in COVID-19 and all studies were published in 2020. The studies were conducted in Brazil 50 , China 13,51-96 , Egypt 97 , France 98-101 , Germany 102 , India 103,104 , Italy [105][106][107][108][109][110][111] , Japan 112,113 , Jordan 114 , Somalia 115 , South Korea 116,117 , Spain 118,119 , Turkey 120,121 , and the US [122][123][124][125][126] . Two studies were cross-sectional 119,122 , five were prospective cohort studies 65,90,98,110,121 and the remaining 71 studies were retrospective studies.…”
Section: Study Eligibility Resultsmentioning
confidence: 99%
“…Few studies from LMIC have been conducted assessing hyposmia or hypogeusia prevalence. In one study from Somalia, up to 80% of patients reported ageusia or anosmia and were the first presenting symptom in about 40% of the cohort with COVID-19 infection [ 41 ].…”
Section: Discussionmentioning
confidence: 99%